2017
DOI: 10.1002/jum.14277
|View full text |Cite
|
Sign up to set email alerts
|

Role of Point Shear Wave Elastography in the Determination of the Severity of Fibrosis in Pediatric Liver Diseases With Pathologic Correlations

Abstract: The VTQ and VTIQ values reveal high-grade histopathologic fibrosis and have high success rates when distinguishing high- from low-grade fibrosis. However, they have limited success rates when differentiating low-grade fibrosis from normal liver tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 18 publications
3
30
2
Order By: Relevance
“…In a series of 75 children, SWV cut offs were 1.67 m/s for pSWE and 1.56 m/s for 2D-SWE in detecting fibrosis or inflammation and 2.09 m/s for pSWE and 2.17 m/s for 2D-SWE in discriminating children with low and high histological liver fibrosis scores. However, both techniques had limited success rates when differentiating low-grade fibrosis from normal liver tissue [14]. In another prospective study, pSWE was feasible in children using both the convex and the linear transducers.…”
Section: Point Swe (Pswe)mentioning
confidence: 99%
“…In a series of 75 children, SWV cut offs were 1.67 m/s for pSWE and 1.56 m/s for 2D-SWE in detecting fibrosis or inflammation and 2.09 m/s for pSWE and 2.17 m/s for 2D-SWE in discriminating children with low and high histological liver fibrosis scores. However, both techniques had limited success rates when differentiating low-grade fibrosis from normal liver tissue [14]. In another prospective study, pSWE was feasible in children using both the convex and the linear transducers.…”
Section: Point Swe (Pswe)mentioning
confidence: 99%
“…Therefore, an association between SWS and pathological processes of the tumors was not able to be established. However, this was not the aim of the present study, as previous studies have demonstrated that the difference in the stiffness is associated with tissue reorganization, particularly fibrosis and necrosis ( 2 , 47 , 52 ). Secondly, the results of these experiments are not directly applicable to human liver cancer tissues: The present tumor model was implanted under the skin of the nude mice.…”
Section: Discussionmentioning
confidence: 86%
“…A variety of elastography techniques have been developed to visualize and quantify the mechanical properties of biological tissues, including thyroid, breast and liver tissues ( 1 , 2 ). In previous years, virtual touch tissue imaging and quantification (VTIQ), a novel two-dimensional shear wave speed (SWS) measurement technique, has been introduced into clinical practice, which not only provides qualitative but also quantitative measurements of the tissue stiffness ( 3 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Sonoelastography, which provides measurement of tissue stiffness, increases the diagnosis and progression of steatosis, and limits the value of early stage diagnosis in diseases such as NAFLD [7] . It has now led to the necessity of understanding the pathology of steatosis with the cause of increased incidence of obesity [7,8].…”
Section: Introductionmentioning
confidence: 99%